Liver cancer mortality in Mexico: trend analysis from 1998 to 2018 - Christian S Álvarez; Priscilla Espinosa-Tamez; Ruy López-Ridaura; Héctor Lamadrid-Figueroa; Javier Melchor-Ruan; Katherine A McGlynn; Martín Lajous (Instituto Nacional de Salud Pública, 2022)
Objective. To examine overall, sex, and state-specific liver cancer mortality trends in Mexico. Materials and methods. Joinpoint regression was used to examine the trends in age-standardized mortality rates of liver cancer between 1998-2018. Estimated annual percent change with 95% confidence intervals (95%CI) were computed. Age-period-cohort models were used to assess the effects of age, calendar year, and birth cohort. Results. The state-specific mortality rates ranged from 3.34 (Aguascalientes) to 7.96 (Chiapas) per 100 000 person-years. Sex-specific rates were roughly equal, nationwide. Overall, we observed a statistically significant decrease in liver cancer mortality rates between 1998-2018 (annual percent change, -0.8%; 95%CI -1.0, -0.6). The overall age-period-cohort models suggest that birth cohort may be the most important factor driving the trends. Conclusions. While there was overall decline in liver cancer mortality, differences in rates by region were observed. The regional differences may inform future studies of liver cancer etiology across the country.